Leakage current and defect characterization of p+n-source/drain diodes - Roll, Guntrade; Goldbach, Matthias; Frey, Lothar (Microelectronics Reliability, 2011)
A good control of the transient enhanced dopant diffusion is needed for MOSFET scaling down to the sub 50 nm regime. Carbon ion implant is known to significantly suppress the transient enhanced boron diffusion. However, carbon implantation is also reported to increase diode leakage current. This paper investigates the impact of ion implantation and annealing conditions during source/drain extension formation on leakage current behavior of boron/phosphorous diodes of PFET transistors. Analyzing the leakage current it is difficult to distinguish between the influence of the increased electric field due to the reduced diffusion and possible additional trap centers in the space charge region. This distinction can be made by electrical characterization, as shown in this paper. The leakage current mechanism is found to be trap assisted tunneling with phonon interaction. The corresponding trap energy within the band gap is 0.58 ± 0.10 eV. The carbon concentration in the space charge region measured by SIMS is below the detection limit. Also in electrical measurements, which are more sensitive, no significant influence of carbon related traps is observed. The leakage current is increased by the application of a Flash Anneal additionally to a Rapid Thermal Anneal for recrystallization of the silicon substrate.